Allelic frequencies and forensic parameters for miniSTRs D10S1248, D14S1434 and D22S1045 (NC01) in a sample from Central Andean Colombian region. (December 2015) - Burgos, G.; Restrepo, T.; Ibarra, A.; Gaviria, A.; Machado, G.; Mora, C.; Lizarazo, R.
Abstract: In this work NC01 (Non CODIS) triplex system (D10S1248, D14S1434 and D22S1045) was chosen for standardization and validation. Allelic ladders were constructed and validated by sequencing. Genotypes for 450 Central Andean Colombian from 6 regions were analysed, population and forensic parameters were estimated, no significant departures from H–W equilibrium were detected and loci were in linkage equilibrium. No signs of homology were detected when NC01 was evaluated on 9 new world primate species. Forensic utility is demonstrated with 25 forensic cases typed with NC01 miniSTRs Triplex.